Pharmacokinetic/Pharmacodynamic Interactions Between Evogliptin and Glimepiride in Healthy Male Subjects - Yoo, Hyounggyoon (Drug Des Devel Ther, 2020)
PURPOSE: Evogliptin, a dipeptidyl peptidase-4 inhibitor, and glimepiride, a sulfonylurea, are used to treat type 2 diabetes mellitus. In this study, we aimed to evaluate the pharmacokinetic (PK) and pharmacodynamic (PD) interactions between evogliptin and glimepiride. MATERIALS AND METHODS: A randomized, open-label, 3-period, 3-treatment, 2-sequence crossover study was conducted in healthy male subjects. During each period, subjects received multiple doses of evogliptin 5 mg alone (EVO), glimepiride 4 mg alone (GLI), or a combination of the two (EVO+GLI). Serial blood and urine samples were collected 168 and 24 h post dosing, respectively, for PK and PD analyses. RESULTS: Thirty-four subjects completed the study. The co-administration of evogliptin and glimepiride did not alter their plasma and urine PK profiles. For evogliptin, the geometric mean ratio (GMR) (90% confidence intervals) for the maximum plasma concentrations at steady-state (C(max,ss)) and the area under the curve during dosing interval at steady-state (AUC(τ,ss)) of EVO+GLI to E were 1.02 (0.98–1.06) and 0.97 (0.95–1.00), respectively. For glimepiride, the corresponding values of EVO+GLI to GLI were 1.08 (1.01–1.17) and 1.08 (1.02–1.14), respectively. All values were within the regulatory bioequivalence criteria of 0.8–1.25. Glucose excursion decreased with the co-administration of evogliptin and glimepiride compared with that observed with the evogliptin or glimepiride monotherapy. CONCLUSION: Evogliptin and glimepiride had no PK interactions when co-administered, while the combination therapy showed an additive glucose-lowering effect compared to those of evogliptin or glimepiride monotherapy.